Blast impact on reinforced concrete wall - Mazlan, Abu Seman (2018)
Reinforced concrete (RC) wall is used as a protective structure to reduce the effect of blast overpressure loading to protect the building, personnel or sensitive equipment from the impact of load via explosion. Even though a number of investigations have been carried out to study the blast impact on RC structures, however it is still lack of experimental and numerical research has been academically published regarding its effect on the RC wall. Most of the published work limited on the RC panel. The published experiment and accessible for reference is the work focuses on different steel reinforcement materials used in RC wall. Thus, further investigation is needed for the RC wall subjected to blast load especially on the appropriate steel reinforcement design and effective arrangement. Present work aims to study the behaviour of RC wall subjected to blast load of 13.61 kg Trinitrotoluene (TNT) at 1.219 m standoff distance from the wall centre experimentally and numerically. The AUTODYN non-linear finite element (FE) analysis commercial software is used to develop a validated numerical model against published experimental result such as recorded blast overpressure data and crack patterns occurred on the RC wall surface. Further numerical parametric investigation for blast impact on RC wall is conducted on the effect of different concrete strengths, steel reinforcement ratios, the hooked direction of vertical flexural reinforcement into the RC wall base and the placing of horizontal steel reinforcement on the vertical steel reinforcement in the RC walls. The present experimental study consisted of three RC walls with similar moment resistance capacity but different steel reinforcement arrangements. The experimental setup similar for RC wall at conflict zone area was considered in the blast field and followed by a validated numerical model. Further numerical assessments were conducted for effective steel reinforcement arrangement in RC wall. The present experimental work established that, the appropriate placement for horizontal steel reinforcement is tied outside on the vertical steel reinforcement or next to the concrete cover. In addition, the hooked-in direction of the vertical steel reinforcement into the wall base indicated that the RC wall behavior is improved in terms of the movement and cracks occurred due to the blast load. The numerical investigation indicated that the RC wall with the horizontal steel reinforcement tied outside on the vertical steel reinforcement is capable to distribute strain and kinetic energy evenly between front and back side of the RC wall. Additionally, with the direction of hooked-out of vertical steel changed to hooked-in into wall base, it is possible to increase spacing on horizontal by 13.16% and vertical steel reinforcement by 33.55% where the RC wall demonstrates a comparable strength and resistance to the initial RC wall’s steel reinforcement spacing of 152 mm horizontal x 152 mm vertical. Therefore, with the appropriate placement of horizontal steel reinforcement in the RC wall, the resistance to the blast load is increased. Furthermore, with the hooked-in of steel reinforcement into the wall base, the effective amount needed for the RC wall subjected to blast load is observed without compromising as the protective structure.